2019
DOI: 10.4315/0362-028x.jfp-18-395
|View full text |Cite
|
Sign up to set email alerts
|

In-Plant Validation Study of Harvest Process Controls in Two Beef Processing Plants in Honduras

Abstract: Imported meat in the United States can become a food safety hazard if proper food safety programs are not fully implemented in foreign meat processing plants. Thus, exporting countries' food safety inspection systems must be equivalent to the U.S. federal inspection system to become eligible to export meat to the United States. The objective of this study was to validate the beef harvest Hazard Analysis and Critical Control Points and food safety programs of two beef processing plants in Honduras operating und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
1
9
0
6
Order By: Relevance
“…Mapping showed that the abattoir environment was stx-positive (12.9%) in most types of samples, while stx detection was lower in surfaces in contact with product (10.8%) than in those not in contact (29.6%). Our results agree with data reported in Honduras before the implementation of improvement actions (Casas et al, 2019). They are also in line with a study conducted in an Argentinean abattoir showing that although operators applied SSOP correctly, stx-positivity was identified in pre-operational samples (Costa at al., 2020).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Mapping showed that the abattoir environment was stx-positive (12.9%) in most types of samples, while stx detection was lower in surfaces in contact with product (10.8%) than in those not in contact (29.6%). Our results agree with data reported in Honduras before the implementation of improvement actions (Casas et al, 2019). They are also in line with a study conducted in an Argentinean abattoir showing that although operators applied SSOP correctly, stx-positivity was identified in pre-operational samples (Costa at al., 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the frequency of stx in carcasses before and after the improvement actions decreased, no significant differences were found, showing that SSOP and GMP reinforcement was not enough to eliminate stx. Thus, the application of combined proven intervention measures as part of an HACCP plan at the end of the slaughter line would be useful to further (Casas et al, 2019). Unlike carcass samples, a significant decrease in the detection of stx in beef cuts (10.1 to 4.8%) was achieved after improvement actions, verifying their success.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations